META-ANALISIS PENGARUH MODEL PEMBELAJARAN MAKE A MATCH TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR - Lahma Ainun Sajidah; Mohammad Taufiq; Muhammad Thamrin; Sri Hartatik (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This study aims to determine the effect of the Make a Match learning model on learning outcomes of elementary school students. The method used in this research is meta-analysis method. This study is to determine whether the Make a Match learning model can improve student learning outcomes. In the next stage, collect relevant articles to collect data. The data was obtained from online journal searches through Google Scholar, where 10 articles were obtained. The keywords used are "Make a Match learning model" and "learning outcomes". Data were obtained and re-analyzed using quantitative methods. Based on the results of the analysis, there is an effect of the Make a Match learning model on student learning outcomes with an average after being given treatment that is 46.946 with an average before being given treatment that is 35.963. So it can be concluded that there is an effect of the Make a Match learning model on the increase in student learning outcomes, namely 10.983.